Dermatomyositis – A Rare Case with Excellent Outcome (Journal of Armed Forces Medical College, Bangladesh, 2022)
Dermatomyositis and Polymyositis are autoimmune rheumatologic diseases with prominent feature of inflammatory myopathy. When the characteristic cutaneous manifestations coexist with myositis it is called dermatomyositis, otherwise it is polymyositis. There are also differences in histological findings. A 25-years-old lady presented with characteristic skin rash and progressive inflammatory proximal myopathy. The patient had difficulty in Activity of Daily Living (ADL) and ultimately she was unable to walk and became bed bound. Her muscle enzymes were very high, MRI and Electromyography (EMG) showed features of inflammatory myopathy (myositis). Muscle biopsy showed typical findings of dermatomyositis. She responded well with steroid and immunosuppressive drug along with exercise, physiotherapy and rehabilitation therapy. Now she is leading almost normal life with minimum maintenance dose of prednisolone and azathioprine.JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 91-94